Access to immigration advice in South West England, 2016-2017 - Marshall, Emma (UK Data Service, 2022)
Data collected in South West England exploring why people seek access to immigration advice, what happens when advice is not available and how to improve access to services in the region. The focus of the data is broadly speaking people with protection-based immigration claims and related human rights. Data were collected during 11 months of fieldwork in the region, semi-structured interviews with people seeking immigration advice, people providing immigration advice and other organisations acting as referral points to legal services. Due to ethical constraints, the data cannot be shared for future reuse. The interview schedules have been uploaded to the record. My PhD research examines how asylum seekers and other people with human rights claims navigate the British immigration system. I am particularly interested in the role that advice plays in mediating the relationship between the state and individuals, in the context of a system where immigration advice is highly regulated and immigration law is exceptionally complex (Law Commission 2020) and access to legal aid has been significantly reduced over the past decade (Singh and Webber 2010; Meyler and Woodhouse 2013; York 2013). The relationship between ideas about who has responsibility for access to justice, and the role of the state within this, is important at a time when policy discourses of austerity and hostile immigration politics have a profound impact on those without legal citizenship and who are unable to afford to pay for private legal advice in relation to their immigration applications. The fellowship is an opportunity for me to develop research to inform justice policy around the impact of the growth of legal aid 'advice deserts' (Burridge and Gill 2017; Wilding 2019) due to the withdrawal of publicly funded legal services. In my PhD, I found that where individuals are unable to access legal aid it can compound and intensify the risks that they face. As part of my PhD research I co-established a clinical legal education project within the University of Exeter Law School, which assists individuals with applications for legal aid through the 'Exceptional Case Funding' scheme. The ECF scheme has been a particularly controversial part of legal aid reform among legal practitioners and the not-for-profit sector (York 2013; Amnesty International 2016). The aim of the clinic is to facilitate greater access to the legal aid system by assisting individuals with applications to secure public funding for their immigration cases. My PhD research was a collaborative project that developed with two partner organisations (Refugee Support Devon and Public Law Project). Through my research I seek to develop academic knowledge alongside practical interventions, and the fellowship will assist in developing these partnerships between the University of Exeter and external organisations. By continuing to develop my research in this area I hope to build a larger research project around the work of university law clinics and the changing dynamics of their work in the UK (Drummond and McKeever 2015), considering the use of technology in immigration advice. There is an opportunity to learn from overseas institutions that are leading in justice innovation, and to exchange knowledge, but attention also needs to be paid to how these schemes are situated within often different types of ideas and debates around the meaning of access to justice. For example, the US has a distinct history of legal advice provision, where debates also exist about the role that universities should play in providing services to the community and facilitating access to justice (Rhode 2009). A priority for my work is considering how university law clinics in the UK can develop their pro bono programmes and opportunities for student education while recognising their own role in shaping the powerful discourses that flow around understandings of the British state and who takes responsibility for the operation of justice systems. The fellowship will allow me to consolidate the impact of my PhD research through publications, with two primary objectives: to contribute to the development of academic knowledge across the disciplines of human geography and law; and, to ensure that my findings are available for use in policy consultation and to the legal and charitable sectors for other forms of policy intervention (for example, policy advocacy and litigation). It will also allow me to develop the trajectory of my research in relation to debates over the use of technology in the justice system and the use of legal innovation to develop new models of advice provision.